Psychology of the Deviant Forms of Economic Personal Behavior in the Cyberspace - Koval, Hanna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The author achieved the defined goal of the research - the psychological features of the deviant forms of economic behavior of an individual in cyberspace were considered. When writing the article, we used a classic set of philosophical and worldview, general scientific methods to implement the problematic completeness of our research and obtain scientifically based and reliable results and general conclusions: synthesis, logic and structure of the presentation, analysis and generalization of the problems of scientific sources. Linguistic methodology and the method of cognition were used to study the problematic issues of this work in the unity of their visual and factual perception, social content, legal and terminological form of representation. The systemic-structural approach made it possible to conceptually form, implement the theoretical foundations and model the complexity of the research discourse. It was noted that crime and delinquency are related to both internal factors that mediate criminal tendencies and external factors such as interaction with other types of crime, age, gender, material values, and the influence of peers. It is concluded that the specifics of deviant forms of individual economic behavior in cyberspace are still not sufficiently studied, and attention is focused more on more popular types of cyber deviance. It was noted that one of the problems is the difficulty of conducting research when referring to various theories and taking into account the key feature of cyberspace - anonymity. At the same time, it is emphasized that the main goal of psychological science is to provide information about current problems, for example, the peculiarities of the formation of economic cyber deviance; detection of a tendency to this type of behavior; planning correctional and educational psychological work with deviants and victims of economic cybercrime.